Analysis of The Influence of Trust, Commitment, Communication, and Complaint Handling on Consumer Loyalty at MDC Trans Lamongan - Evi Fitrotun Najiah; Luluk Nur Azizah; Henny Mahmudah (Jurnal Multidisiplin Sahombu, 2025)
The development of the business world is moving very fast due to the wide open globalization for business actors. Many companies consider that loyal consumers will be able to improve the long-term survival of the company. The purpose of this study is to determine how trust, commitment, communication and complaint handling influence consumer loyalty, so that the following hypothesis is proposed: It is suspected that trust, commitment, communication, and complaint handling have an influence on consumer loyalty partially and simultaneously. and it is suspected that the complaint handling variable is the dominant variable that influences consumer loyalty. MDC Trans Lamongan services. The results of the analysis show that all collected data are valid and reliable, there is no multicollinearity and heterocollinearity. The SPSS output results also show that the multiple correlation value is 0.971 and the coefficient of determination (R2 ) is 0.944. From the t-table calculation, the results are 1.9921 and the calculated t X1 is 2.233 X2 is 6.636. X3 is 4.487 and X4 is 6.209, indicating that there is a partial or individual influence. Meanwhile, after the f-table calculation, the f-table value is 2.49 and the calculated f is 313.933, indicating that there is a simultaneous or joint influence. Meanwhile, from the multiple linear regression analysis test, the value of Y = -4.444 + 0.199 X1 + 0.498 X2 + 0.304 X3 + 0.652 X4 is obtained. The conclusion of this study is that there is a partial influence shown based on the t-test which explains that the Trust variable has a significant positive effect on Consumer Loyalty. There is a simultaneous influence known from the F test that Trust, Commitment, Communication, and Complaint Handling have a significant positive effect on Loyalty, and it is known that the complaint handling variable is the variable that has the most influence on Consumer Loyalty.